DETERMINAÇÃO ELETROANALÍTICA DO HERBICIDA PARAQUAT EM SOLUÇÕES AQUOSAS SOBRE ELETRODOS MODIFICADOS COM O SISTEMA QUITOSANA - NiTsPc - Corrêa, Gláucia Tinoco (2013)
A glassy carbono electrode (GC) modified with nickel tetrasulfonated phthalocyanine (NiTsPc) and chitosan (CT) film was used to determine paraquat (PQ) in aqueous solutions with cyclic (CV), differential pulse (DPV) and square wave (SWV) voltammetry techniques. The cyclic voltammetry experiments in phosphate buffer solutions (pH 7) containing PQ showed an reversible peak near - 0,70 V vs Ag/AgCl on the GC/QT-NiTsPc electrode, shifted to about 100 mV to less positive value and with much higher reduction currents as compared to the data recorded on the GC/CT electrode. The CT-NiTsPc film was characterized by infrared spectroscopy. The best experimental conditions to modify the GC electrode with the CT-NiTsPc films and to determine PQ with the CV, DPV and SWV techniques were established. The analytical curves obtained with the SWV technique presented the best detection and quantification limits and it was successfully used to determine PQ in natural water with 101,33 % recovery and in agreement with the results obtained with high-performance liquid chromatography.